Topical intrawound application of vancomycin powder in addition to intravenous administration of antibiotics: a meta-analysis on the deep infection after spinal surgeries - Xiong, Lingyun; Hirche, Christoph (Orthopaedics & traumatology, 2014)
Background: The intrawound application of vancomycin powder in addition to intravenous administration of antibiotics has been reported to be an easy and cost-efﬁcient technique for reducing the deep infection, which is a serious complication of spinal surgeries. The aim of the present meta-analysis was to derive a preliminary estimation on the clinical performance of this technique.